Understanding human error in aviation - Majić, Jadranka (Crisis Management Days, 2024)
Error is an integral part of human performance, resulting from physiological and psychological limitations inherent in humans. It has been a contributing factor to the majority of incidents and accidents in any field of human activity. Approximately 80% of aviation events are caused by a decrease in human performance. As aviation safety depends on minimising error in all constituents of this compound system, it is primarily important to classify errors in order to better understand their nature and causes, and investigate them. A holistic approach to error also needs to be taken for its investigation and analysis, since humans do not act in isolation. Human performance is a complex process, influenced by work environment, technology, various cultural aspects and other participants in it. A mismatch in interaction of humans and other components in this process leads to error, and therefore it must be scrutinised in all facets of the aviation system. While errors resulting in incidents, accidents and loss of life are mostly made by pilots or air traffic controllers and draw more attention, those made by maintenance staff also need to be taken seriously, since they can result in fatalities and damage to aircraft as well, and entail significant consequences to air traffic. Methods of researching human error in the aviation context will range from studying event databases, self-reports and accident reports to case studies. Typical examples of human error that contributed to various safety occurrences will be analysed, with its causes, lessons learnt and remedies stated. The aim of comprehending why people make errors is to elaborate safety recommendations and technological solutions that will decrease the likelihood of aviation events, and mitigate the consequences. Errors can be managed and reduced primarily by creating an error-tolerant environment rather than punitive environment, improving error training, and using a number of technological models, aids and methods, including the threat and error management concept. Human error cannot be eliminated, but by understanding its origin and cause, as well as learning from these experiences, the occurrence of incidents and accidents can be reduced, and the effects minimised.